IMAJINASI KEINDAHAN IKAN CUPANG HIAS DALAM FOTOGRAFI SENI - Dede Bilal Kurniawan; Amoga Lelo Octaviano; I Made Bayu Pramana (Retina Jurnal Fotografi, 2021)
The limitation social is a tactical move that is applied by the government in the prevention of transmission of the virus Covid-19. The time duration of the entry into force of the social restrictions that are long enough, so that people trying to find positive activities that can be done at home respectively. Maintain betta fish ornamental is one of the positive event that the author did. Ornamental betta fish is a kind of freshwater fish that can be found and spread in tropical waters. Ornamental betta fish has the form type of the fins and tail are unique and colorful. This is the basic idea for the author to explore imajination the beauty of betta fish ornamental in art photography. In the process of the creation of masterpieces of photography the author uses the method of creation by making observations of the object so created an idea. Of the idea continued stage design with imagination and collection references. After that, further to stage a photo shoot and stage image processing by combining the theory of aesthetic and color theory to produce photographic works in accordance with the theme that is created. Betta fish have the beauty of fin shapes and colors that are very interesting unique if visualized in art photography with obstacles are looking poses betta fish which is in accordance with the wishes of the author. The result of the creation of this work the author is steeped in the beauty of betta fish decorative from a variety of fins and the color is unique. The author did a photo shoot in the studio with the use of artificial light in the form of flash). Keywords : Imagination, Beauty, Betta Fish, Art Photography